Design And Analysis Of Cold Forged AUV Propeller - Bakar, Muhamad Husaini Abu (2011)
Most of power of an Autonomous Underwater Vehicle (AUV) is utilized by its propulsion system. Since AUV power only depends on onboard battery, the power consumption becomes crucial issue in optimizing the AUV performance. In this research a propeller need to be fabricated for AUV that will be developed by Underwater Robotic Research Group (URRG). The specific propeller design must be discovered in order to optimize the AUV power consumption. PVL code that has been developed by Kerwin (2001) was used as a tool to design the specific propeller.